a APPLICATION OF PROBIOTIC TECHNOLOGY IN FEED TO INCREASE NILE TILAPIA AQUACULTURE PRODUCTIVITY - Nurfika Ramli, S.Pi., M.Si (MALLOMO: Journal of Community Service, 2026)
The high production cost, especially the feed component which accounts for 60–70% of total operational costs , is a major challenge for Nile tilapia farmers in Purnakarya Village. To address this issue, this community service program aims to introduce and apply probiotic technology in feed as a strategy to improve nutritional efficiency, growth, and health of Nile tilapia. The implementation method used a participatory and educative approach , consisting of socialization, counseling, training and demonstration of probiotic application in feed, followed by periodic mentoring and monitoring in the field. The evaluation results showed a significant increase in the partners' knowledge and skills regarding the formulation of probiotic-enriched feed. Technically, the application of probiotic feed during the rearing period successfully increased fish weight growth by ±25%, achieved a survival rate (SR) of up to 90%, and improved the feed conversion ratio (FCR) to 1.4. In conclusion, the application of probiotic technology is an appropriate innovation that is easy to implement, economical, and effectively increases both the productivity of Nile tilapia aquaculture and the independence of the farmers.